Ten simple rules for neuroimaging meta-analysis. (January 2018) - Müller, Veronika I.; Cieslik, Edna C.; Laird, Angela R.; Fox, Peter T.; Radua, Joaquim; Mataix-Cols, David; Tench, Christopher R.; Yarkoni, Tal; Nichols, Thomas E.; Turkeltaub, Peter E.; Wager, Tor D.; Eickhoff, Simon B.
Highlights: Meta-analyses require a consistent approach but specific guidelines are lacking. Best-practice recommendations for conducting neuroimaging meta-analyses are proposed. We set standards regarding which information should be reported for meta-analyses. The guidelines should improve transparency and replicability of meta-analytic results. Abstract: Neuroimaging has evolved into a widely used method to investigate the functional neuroanatomy, brain-behaviour relationships, and pathophysiology of brain disorders, yielding a literature of more than 30, 000 papers. With such an explosion of data, it is increasingly difficult to sift through the literature and distinguish spurious from replicable findings. Furthermore, due to the large number of studies, it is challenging to keep track of the wealth of findings. A variety of meta-analytical methods (coordinate-based and image-based) have been developed to help summarise and integrate the vast amount of data arising from neuroimaging studies. However, the field lacks specific guidelines for the conduct of such meta-analyses. Based on our combined experience, we propose best-practice recommendations that researchers from multiple disciplines may find helpful. In addition, we provide specific guidelines and a checklist that will hopefully improve the transparency, traceability, replicability and reporting of meta-analytical results of neuroimaging data.